Spätmoderne Predigt im Entwurf einer gastlichen Gottesrede - Beck, Wolfgang (Zeitschrift für Theologie und Kirche, 2023)
The approach of a "hospitable preaching" is located in the cross-denominational effort to define Christian preaching and possible speech of God in the contexts of late-modern societies. In this article, the approach is presented in dialogue with the art installation "The Artist is Present" by Marina Abramović and thus is concerned with performing a mediation between the mutual penetration of theological reflection and the contemporary cultural exchange. In this concern, the sermon is taken seriously as a public speech and developed further as a "communication of the gospel".